ORGANIZATIONAL DEVELOPMENT THROUGH THE FORMATION OF A CULTURE OF RESPONSIBILITY AND SELF-ORGANIZATION OF EMPLOYEES (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article examines organizational development through the lens of fostering a culture of responsibility and employee self-organization. Drawing on modern psychological and management theories, it analyzes the mechanisms by which autonomy, distributed responsibility, and a supportive organizational context contribute to increased organizational effectiveness, adaptability, and resilience. Empirical data confirming the link between a culture of responsibility and employee engagement, productivity, and innovative behavior are summarized. Practical directions for developing self-organizing work systems in modern organizations are proposed.